Sudan : Staff-Monitored Program-Press Release; Staff Report; and Statement by the Executive Director for Sudan. (IMF Staff Country Reports; Country Report ;, 2020)
The transitional government has requested a Staff-Monitored Program (SMP) to help address major macro imbalances, lay the groundwork for inclusive growth, and establish a track record of sound policies that is a requirement for eventual HIPC debt relief. Major challenges lie ahead. Economic contraction since 2018 is set to intensify sharply in 2020 as a result of the COVID-19 pandemic. Fiscal and external imbalances are large, inflation is high and rising, the currency is overvalued, and competitiveness is weak. The humanitarian situation is dire with large numbers of internally displaced people and refugees. Despite the desperate situation, Sudan cannot access Fund financial assistance on account of (i) arrears to the Fund, (ii) arrears to other IFIs and other creditors, and (iii) unsustainably large external debt. Sudan remains on the U.S. state sponsors of terrorism list (SSTL), which effectively hinders progress toward HIPC debt relief. While there is broad agreement between the authorities and staff about the key reform priorities, public tolerance for painful reforms is fragile given prolonged economic hardship. Notably, donor financial assistance has been well short of the amounts needed to facilitate gradual orderly adjustment. Hence, risks to the SMP are high.